Content Matters, a Qualitative Analysis of Verbal Hallucinations - Moernaut, Nienke; Vanheule, Stijn; Feyaerts, Jasper (Frontiers in Psychology, 2018)
Auditory verbal hallucinations have traditionally especially been researched from a form-based approach, with content getting much less attention. In this article, we argue for the importance of looking at content to get a fuller understanding of the hallucinatory experience. Guided by Lacanian psychoanalysis, we conducted a thematic and a narrative analysis on interviews with 10 schizophrenic patients about their hallucinations. We discerned 5 themes in the data, which were based on Lacanian theory and had to do with existential questions: parenthood and authority, sexuality and relationships, gender identity, life in the light of death and what does the other want? Furthermore, we added a theme for unclassified content. Narratively, we found that participants constructed a story of 4 steps about their hallucinatory experiences. These steps were disturbing events in the past posing an existential question, triggering event, period of confusion and hearing voices that allude to existential themes. Participants succeed in different degrees in integrating their hallucinatory experiences in their own life history. These stories can be situated on a continuum by making use of three prototypical narrating styles: the meta-delusional, delusional, and chaotic narrative type. Overall, our analysis shows that hallucinations can both be thematically and narratively organized, by making use of a theoretical framework like Lacanian psychoanalysis. Our research demonstrates that hallucinatory contents are not random but are about existential issues imbedded in a life narrative. Future research would benefit of integrating content and form-based approaches.